2022
DOI: 10.3389/fphys.2022.927221
|View full text |Cite
|
Sign up to set email alerts
|

Immune remodeling and atrial fibrillation

Abstract: Atrial fibrillation (AF) is a highly prevalent arrhythmia that causes high morbidity and mortality. However, the underlying mechanism of AF has not been fully elucidated. Recent research has suggested that, during AF, the immune system changes considerably and interacts with the environment and cells involved in the initiation and maintenance of AF. This may provide a new direction for research and therapeutic strategies for AF. In this review, we elaborate the concept of immune remodeling based on available d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 130 publications
0
28
0
Order By: Relevance
“…Recent studies have shown that considerable changes in the immune system occur during AF, including the recruitment and activation of immune cells and the secretion of their immune molecules induced by various factors; this is a process called immune remodeling (33). Immune remodeling runs through the entire process of the occurrence and maintenance of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that considerable changes in the immune system occur during AF, including the recruitment and activation of immune cells and the secretion of their immune molecules induced by various factors; this is a process called immune remodeling (33). Immune remodeling runs through the entire process of the occurrence and maintenance of AF.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that COPD-induced structural changes in the heart, increased sympathetic activity, and hypoxia-induced oxidative stress accelerates the development of AF. But recent studies have highlighted the role of immune dysfunction in the pathogenesis of both diseases, finding that immune dysfunction may play a prominent role in the subsequent inflammatory response, cardiac remodeling, structural remodeling, and neural remodeling ( 11 , 38 ). However, the exact mechanisms have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms lead to increased ectopic atrial activity as well as slow and heterogenous atrial conduction resulting in abnormal atrial depolarizations and the promotion of re-entry circuits [18]. Additionally, systemic inflammation induces endocardial and endothelial inflammation facilitating atrial remodeling [18]. Various inflammatory mediators are implicated in these processes including TNF-α, IL-2, and platelet-derived growth factor (PDGF) [6,11].…”
Section: Contemporary Pathophysiology Of Atrial Fibrillation In the C...mentioning
confidence: 99%